2021
DOI: 10.1038/s41467-021-25449-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric biomimetic transamination of α-keto amides to peptides

Abstract: Peptides are important compounds with broad applications in many areas. Asymmetric transamination of α-keto amides can provide an efficient strategy to synthesize peptides, however, the process has not been well developed yet and still remains a great challenge in both enzymatic and catalytic chemistry. For biological transamination, the high activity is attributed to manifold structural and electronic factors of transaminases. Based on the concept of multiple imitation of transaminases, here we report N-quate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Aliphatic alkylamines are abundant feedstock and versatile building blocks in a variety of important biological and synthetic transformations through the construction and activation of their C–N bonds . A number of redox- and non-redox-based biological processes invoke the cleavage of C–N bonds, such as ubiquitous transamination, , cross exchange of an amino group and a hydrogen atom on vicinal carbon atoms, and deaminative conversion of alkylamine to aldehyde. , In particular, deaminative oxidations of primary alkylamines are typically catalyzed by amine oxidases, including the copper-containing amine oxidases (CuAOs) and the flavin-containing monoamine and polyamine oxidases (MAOs and PAOs), , to form aldehydes and ammonia: RCH 2 NH 2 + H 2 O + O 2 → RCHO + NH 3 + H 2 O 2 . This reaction affords the oxidation of the α-carbon site on the alkyl chain instead of the nitrogen atom of the amino group upon the cleavage of the C–N bond.…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic alkylamines are abundant feedstock and versatile building blocks in a variety of important biological and synthetic transformations through the construction and activation of their C–N bonds . A number of redox- and non-redox-based biological processes invoke the cleavage of C–N bonds, such as ubiquitous transamination, , cross exchange of an amino group and a hydrogen atom on vicinal carbon atoms, and deaminative conversion of alkylamine to aldehyde. , In particular, deaminative oxidations of primary alkylamines are typically catalyzed by amine oxidases, including the copper-containing amine oxidases (CuAOs) and the flavin-containing monoamine and polyamine oxidases (MAOs and PAOs), , to form aldehydes and ammonia: RCH 2 NH 2 + H 2 O + O 2 → RCHO + NH 3 + H 2 O 2 . This reaction affords the oxidation of the α-carbon site on the alkyl chain instead of the nitrogen atom of the amino group upon the cleavage of the C–N bond.…”
Section: Introductionmentioning
confidence: 99%
“…The α-ketoamide subunit is present in many natural and nonnatural biologically active molecules, drug candidates, and marketed drugs, with multiple therapeutic indications. 1 The electron-deficient keto carbonyl group activated by an amide may interact with the hydroxyl residue of an enzyme to agonize or inhibit biological actions. 1 b – d For example, studies have shown that an α-ketoamide-containing reversible inhibitor can covalently bind to HCV NS3 serine protease.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the role of transaminase based on the PLP-Lys active structure, Zhao's group designed and synthesized a variety of axially chiral organocatalysts for realizing biomimetic asymmetric transamination reactions. [30][31][32]65 Notably, they developed an enantioselective Mannich reaction with an axially chiral pyridoxal catalyst for generating diamino acid ester in 93% yield with a >20 : 1 diastereomeric ratio (dr) and 98% enantiomeric excess (ee). 33 These kinds of biomimetic asymmetric reactions have achieved great progress in the biomimetic catalysis field, but the corresponding mechanistic study still lags behind.…”
Section: Introductionmentioning
confidence: 99%